2015
DOI: 10.1097/mpg.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Natural History, and Outcome of Acute Fluid Collection and Pseudocyst in Children With Acute Pancreatitis

Abstract: Among children with AP, 58.6% developed AFC and 38% developed pseudocysts. Only patients with symptomatic pseudocyst need drainage, and asymptomatic pseudocyst can be safely observed irrespective of size and duration of collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 25 publications
1
32
0
2
Order By: Relevance
“…In a study conducted by 7 centers, only one pediatric patient out of 380 developed necrosis 12,20,32 . Other studies found the incidence of multiple organ failure and pancreatic necrosis to be under 10% 32,106 , while the incidence of pseudocysts ranged 10-38% 32,106 . The mortality was 2-11%, mostly associated with systemic diseases 107,108 .…”
Section: Ap-vii Treatment Of Complications In Pediatric Apmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by 7 centers, only one pediatric patient out of 380 developed necrosis 12,20,32 . Other studies found the incidence of multiple organ failure and pancreatic necrosis to be under 10% 32,106 , while the incidence of pseudocysts ranged 10-38% 32,106 . The mortality was 2-11%, mostly associated with systemic diseases 107,108 .…”
Section: Ap-vii Treatment Of Complications In Pediatric Apmentioning
confidence: 99%
“…Complicated or symptomatic pseudocysts should be treated 112 . There are reports of successful EUS-guided drainage of pseudocysts in children 106,109 . medications, smoking, alcohol) ones also can elevate the risk of developing CP.…”
Section: Ap-vii5 What Are the Indications For Intervention In The Pmentioning
confidence: 99%
“…[2][3][4] In spite of the growing awareness, pancreatitis is associated with considerable morbidity in children. 6 Drainage of PFC can be achieved by endoscopic, percutaneous or surgical methods. Acute fluid collections (<4 weeks old) are usually asymptomatic and most resolve spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, about 40% of pseudocysts develop symptoms requiring drainage. 6 Drainage of PFC can be achieved by endoscopic, percutaneous or surgical methods. However, endoscopic modality of drainage is associated with less morbidity and is, therefore, the initial drainage modality of choice in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, acute fluid collection developed in 58.6% of children with AP. However, pseudocyst developed in 38% and drainage was required in only 26.4% of these 10. Asymptomatic PFCs can be managed conservatively.…”
Section: Introductionmentioning
confidence: 99%